PENGARUH PERSEPSI HARGA, KEPERCAYAAN, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT. SINAR TRANS GLOBAL (KASUS JASA PELAYANAN BONGKAR CURAH IMPOR) - Erik Prasetya; Makmun Riyanto; Suwardi Suwardi (Politeknik Negeri Semarang, 2017)
This research was aimed to find out the influence price perception, trust, service quality toward customer satisfaction in PT Sinar Trans Global. The methods of data collection were interview and questionnaire completion. The sample of this research are 42 respondents and analytical method used were the validity test, reliability test, multiple linear regression conducted with the Ordinary Least Square (OLS) test methods and Goodness of Fit Test. The result of regression analysis indicated that price perception, trust, quality service had positive influence on customer satisfaction. Based on t test it was indicated that price perception, trust, quality service had positive significant influenced on customer satisfaction. Based on F test, independent variables simutaneuosly influenced the customer satisfaction significantly, with coeficient of determination (R2) of 0,910. This means that 91% of customer satisfaction could be influenced by price perception, trust, quality service while the remaining of 9% was influenced by other variables which were not observed.